Implementasi Permendikbud Nomor 12 Tahun 2015 tentang Program Indonesia Pintar (Pada Pelajar SMP Negeri 4 Bontoramba Kabupaten Jeneponto) - SB, Karina.; Kasmawati, Andi; Suyitno, Imam (Jurnal Tomalebbi, 2024)
This research aims to determine the planning, implementation and evaluation as well as the obstacles that arise in providing the Smart Indonesia Program (PIP) for students at SMP Negeri 4 Bontoramba. The type of research used in this research is qualitative using a qualitative descriptive approach. Data collection procedures are observation, interviews and documentation. The data analysis used is data reduction, data presentation, verification and drawing conclusions. The results of the research show that: 1) Planning for providing the Indonesian Program (PIP) at SMP Negeri 4 Bontoramba was carried out by (a) Entering a list of names of students in the Basic Education Data or usually abbreviated as Dapodik, (b) Proposing potential students to receive BSM/PIP funds , (c) Monitoring the process of collecting funds for Poor Student Assistance or usually abbreviated as BSM/PIP, and (d) Accepting children aged 6 (six) to 21 (twenty one) years old holders of Smart Indonesia Cards or usually abbreviated as KIP who have not/dropped school. 2) The implementation of the Smart Indonesia Program (PIP) is based on the PIP Implementation Principles, namely (a) Efficient, (b) Effective, (c) Transparent, (d) Accountable, (e) Appropriateness, and (f) Benefits.  And 3) Evaluation and reporting of the Smart Indonesia Program evaluation is carried out every time the Evaluation Program funds provided for the Smart Indonesia Program have been given in accordance with the Monitoring and evaluation of article 15 of Minister of Education and Culture Regulation Number 12 of 2015 concerning Monitoring and evaluation of PIP implementation carried out by the relevant directorate general, provincial education office, and /or the district/city education office according to their authority. 4) The obstacle in implementing Minister of Education and Culture Regulation Number 12 of 2015 is that the Evaluation of the Smart Indonesia Card Program which is carried out in each period causes changes, especially in the mechanism, especially for students who do not have a Smart Indonesia Card (KIP) who cannot receive the Smart Indonesia Program even though these students are classified as high achieving students and are economically disadvantaged, because the Smart Indonesia Program can only be obtained by those whose names are recorded as students receiving the Program.